RELIGION VALUE IN NOVEL: KETIKA CINTA BERTASBIH” KARYA HABIBURRAHMAN EL SHIRAZY ( STRUCTURAL GENETIC APPROACH) - Kholid, M. Ridho (Universitas Islam Negeri Raden Intan Lampung, 2015)
This research is aimed at searching for the religious values on Habburrahman El Shirazy’s novel entitled Ketika Cinta Bertasbih by applying Genetic Structuralism using descriptive method and content analysis technique. The approaches used in this research were the sociology of literature and religiousness of literature. The religious values existing on this novel included as one of missionary endeavor forms, which gave valuable learning and enrich moral value. By means of his work of art, novel in this case, the author tried to present the sociological condition within his society. He also tried to deliver a missionary endeavor by using familiar language expressions, it was because the language of the novel was easily understood by the readers and the theme of the novel was closely related to the society condition. Sociological approach depicted that Ketika Cinta Bertasbih really influenced social values existed within the society, and the reverse. An author’s background absolutely gave great influence a novel, so did on this novel. Therefore, the social life of Habiburrahman El Shirazy had close relationship with his novel, Ketika Cinta Bertasbih.